‘You’re basically naked’: a qualitative study of why girls drop out of sport in their teenage years - Jane Ogden; Abigail McCourt; Rebecca Morgan (Cogent Psychology)
Objective: This qualitative study explored why a disproportionate number of girls drop out of sport as teenagers. Methods: Women (n=20) aged 18-25 who had dropped out of ballet, swimming and gymnastics in adolescence took part in interviews with a photograph-promoted think-aloud component. Results: Thematic Analysis described four main themes: ‘Internal and external pressures’ such as striving for sporting excellence, pressure from others and the need for academic achievement; ‘Body exposure’ including revealing uniforms and body concerns; ‘Gender roles’ focussing on unfair stereotypes and the need to be true to themselves and ‘The Final Straw’ including a ceiling effect, fear of missing out and puberty. Transcending these themes was the notion of ‘Making constant comparisons’ highlighting unhealthy upward comparisons by oneself, of others and from others. Finally, overarching all themes was ‘Lessons to my younger self’ emphasising fun rather than just competing and being kinder to oneself. Conclusion: Overall, young girls often leave sport due to constant upward comparisons of what their body does and what it looks like exacerbated by the sporting environment. They tell their younger selves to be more present-orientated focussing on sport as fun and for friendship and to be kinder to their bodies. Then they might have stayed.